Biotic factors limit the invasion of the plague pathogen ( Yersinia pestis ) in novel geographical settings - Henry G. Fell; Owen G. Osborne; Matthew D. Jones; Steve Atkinson; Simon Tarr; Suzanne H. Keddie; Adam C. Algar (Global Ecology and Biogeography, 2022)
Aim The distribution of Yersinia pestis , the pathogen that causes plague in humans, is reliant upon transmission between host species; however, the degree to which host species distributions dictate the distribution of Y. pestis , compared with limitations imposed by the environmental niche of Y. pestis per se, is debated. We test whether the present‐day environmental niche of Y. pestis differs between its native range and an invaded range and whether biotic factors (host distributions) can explain observed discrepancies. Location North America and Central Asia. Major taxa studied Yersinia pestis . Methods We use environmental niche models to determine whether the current climatic niche of Y. pestis differs between its native range in Asia and its invaded range in North America. We then test whether the inclusion of information on the distribution of host species improves the ability of models to capture the North American niche. We use geographical null models to guard against spurious correlations arising from spatially autocorrelated occurrence points. Results The current climatic niche of Y. pestis differs between its native and invaded regions. The Asian niche overpredicted the distribution of Y. pestis across North America. Including biotic factors along with the native climatic niche increased niche overlap between the native and invaded models, and models containing only biotic factors performed better than the native climatic niche alone. Geographical null models confirmed that the increased niche overlap through inclusion of biotic factors did not, with a couple of exceptions, arise solely from spatially autocorrelated occurrences. Main conclusions The current climatic niche in Central Asia differs from the current climatic niche in North America. Inclusion of biotic factors improved the fit of models to the Y. pestis distribution data in its invaded region better than climate variables alone. This highlights the importance of host species when investigating zoonotic disease introductions and suggests that climatic variables alone are insufficient to predict disease distribution in novel environments.

Nutrient recycling by insect and fish communities in high-elevation tropical streams - Carla L. Atkinson; Alexander V. Alexiades; Keeley L. MacNeill; Andrea C. Encalada; Steve A. Thomas; Alexander S. Flecker (Hydrobiologia, 2019)

Determinants of food resource assimilation by stream insects along a tropical elevation gradient - Carla L. Atkinson; Andrea C. Encalada; Amanda T. Rugenski; Steve A. Thomas; Andrea Landeira-Dabarca; N. LeRoy Poff; Alexander S. Flecker (Oecologia, 2018)

Interference with the germination and growth of U lva zoospores by quorum‐sensing molecules from U lva ‐associated epiphytic bacteria - Matthew S. Twigg; Karen Tait; Paul Williams; Steve Atkinson; Miguel Cámara (Environmental Microbiology, 2014)
Summary U lva zoospores preferentially settle on N ‐acylhomoserine lactone ( AHL ) producing marine bacterial biofilms. To investigate whether AHL signal molecules also affect the success and rate of zoospore germination in addition to zoospore attraction, the epiphytic bacteria associated with mature U lva linza were characterized and bacterial isolates representative of this community tested for the ability to produce AHLs . Two of these AHL ‐producing isolates, S ulfitobacter spp. 376 and S hewanella spp. 79, were transformed with plasmids expressing the B acillus spp. AHL lactonase gene aii A to generate AHL ‐deficient variants. The germination and growth of U . linza zoospores was studied in the presence of these AHL ‐deficient strains and their AHL ‐producing counterparts. This revealed that the AHLs produced by S ulfitobacter spp. and S hewanella spp. or the bacterial products they regulate have a negative impact on both zoospore germination and the early growth of the U lva germling. Further experiments with E scherichia coli biofilms expressing recombinant AHL synthases and synthetic AHLs provide data to demonstrate that zoospores germinated and grown in the absence of AHLs were significantly longer than those germinated in the presence of AHLs . These results reveal an additional role for AHLs per se in the interactive relationships between marine bacteria and U lva zoospores.

The Arctic Coastal Dynamics Database: A New Classification Scheme and Statistics on Arctic Permafrost Coastlines - Hugues Lantuit; Pier Paul Overduin; Nicole Couture; Sebastian Wetterich; Felix Aré; David Atkinson; Jerry Brown; Georgy Cherkashov; Dmitry Drozdov; Donald Lawrence Forbes; Allison Graves-Gaylord; Mikhail Grigoriev; et al. (Estuaries and Coasts, 2012)

Turnover of quorum sensing signal molecules modulates cross‐kingdom signalling - Karen Tait; Holly Williamson; Steve Atkinson; Paul Williams; Miguel Cámara; Ian Joint (Environmental Microbiology, 2009)
Summary N ‐acylhomoserine lactone (AHL) quorum‐sensing molecules modulate the swimming behaviour of zoospores of the macroalga Ulva to facilitate the location of bacterial biofilms. Here we show that the intertidal surfaces colonized by Ulva are dominated by Alphaproteobacteria , particularly the Rhodobacteraceae family, and the Bacteroidetes family Flavobacteriaceae , and that this diverse assemblage both produces and degrades AHLs. N ‐acylhomoserine lactones could also be extracted from the surfaces of pebbles recovered from intertidal rock‐pools. Bacteria representative of this assemblage were isolated and tested for the production and degradation of AHLs, and for their ability to modulate zoospore settlement at different biofilm densities. Of particular interest was a Shewanella sp. This strain produced three major AHLs (OC4, OC10 and OC12) in the late exponential phase, but the longer‐chain AHLs were rapidly degraded in the stationary phase. Degradation occurred via both lactonase and amidase activity. A close relationship was found between AHL synthesis and Ulva zoospore settlement. The Shewanella isolate also interfered with AHL production by a Sulfitobacter isolate and its ability to enhance zoospore settlement in a polymicrobial biofilm. This influence on the attachment of Ulva zoospores suggests that AHL‐degrading strains can affect bacterial community behaviour by interfering with quorum sensing between neighbouring bacteria. More importantly, these interactions may exert wider ecological effects across different kingdoms.

Common Data Formats - Larry Atkinson; Steve Hankin (Oceanography, 1995)